Broadband power line communication channel modeling based on Q3D - Wangbin CAO; Xiaolin LIANG (Dianxin kexue)
A method of broadband power line communication (PLC) channel modeling based on Q3D extractor was proposed. The per unit length RLGC parameters of PLC channel was extracted by the Q3D extractor. Then, the ABCD transfer matrix of power line channel was calculated based on the extracted RLGC parameters. Finally, the amplitude and phase frequency responses of the channel transfer function and input impedance were obtained by using ABCD matrix. Based on the proposed method, a broadband PLC channel model for 3 mm×4 mm symmetrical cable was set up. The calculated results show that the simulated results fit the measured results well. The proposed method can quickly and accurately establish the broadband PLC channel model, which is of great significance for studying the characteristics of PLC channel.